THE ROLE OF PRAGMATICS IN TRANSLATION - Soyibnazarov, Navruz (Журнал иностранных языков и лингвистики, 2021)
The main purpose of this article is to study the relationship between the two areas, translation and pragmatics, while distinguishing between them, and to identify the specifics of translation pragmatics.